The secret battle of Evan Pao - Shang, Wendy Wan Long (Scholastic Press, 2022)
Evan Pao and his family move to Haddington, Virginia in hopes of keeping his father's notoriety a secret, but a small southern town is not an easy place for a Chinese-American boy to fit in, and one kid, Brady Griggs, seems determined to make things difficult.